Intimate partner violence is a significant risk factor for adverse pregnancy outcomesAJOG Global Reports at a Glance - Elizabeth P. Lockington, MD; Helen C. Sherrell, FRANZCOG, PhD; Kylie Crawford, FANZCVS, PhD; Kym Rae, PhD; Sailesh Kumar, FRCS, FRCOG, FRANZCOG, DPhil (Oxon) (Elsevier, 2023)
BACKGROUND: Globally, almost 30% of women report experiencing intimate partner violence. In Australia, intimate partner violence is estimated to affect 2.0% to 4.3% of pregnant women. Those who experience intimate partner violence during pregnancy have poorer perinatal and maternal outcomes, including preterm birth, low birth weight, preterm prelabor rupture of membranes, perinatal death, miscarriage, antepartum hemorrhage, maternal trauma, and death. OBJECTIVE: This study aimed to evaluate the maternal and perinatal outcomes among women who reported intimate partner violence in a tertiary Australian hospital. STUDY DESIGN: This was a retrospective observational study conducted between January 2017 and December 2021 at the Mater Mother's Hospital in Brisbane, Australia. The study cohort included pregnant women who completed a prenatal intimate partner violence questionnaire. Exclusion criteria included infants with known major congenital or chromosomal abnormalities. RESULTS: Of the total study cohort comprising 45,177 births, 3242 births (7.2%) were among women who were exposed to intimate partner violence. Those who identified as Indigenous or had refugee status experienced significantly higher rates of intimate partner violence. Women exposed to intimate partner violence had greater odds of having a small for gestational age infant (adjusted odds ratio, 1.17; 95% confidence interval, 1.04-1.33), preterm birth (adjusted odds ratio, 1.21; 95% confidence interval, 1.07-1.37), preterm prelabor rupture of membranes (adjusted odds ratio, 1.23; 95% confidence interval, 1.05-1.45), and an infant with severe neonatal morbidity (adjusted odds ratio, 1.21; 95% confidence interval, 1.08-1.35). Women who reported intimate partner violence also had higher odds of acute presentation to the obstetrical assessment unit (adjusted odds ratio, 1.71; 95% confidence interval, 1.58-1.85) and admission to hospital (adjusted odds ratio, 1.44; 95% confidence interval, 1.30-1.61). When compared with non-Indigenous women exposed to intimate partner violence, Indigenous women had worse outcomes with significantly higher rates of preterm prelabor rupture of membranes, extreme preterm birth, lower gestational age at birth, low birth weight, and higher rates of infants with birth weight <fifth percentile for gestation. CONCLUSION: Intimate partner violence is associated with increased risks for poor perinatal outcomes, particularly among those who identify as Indigenous and those with refugee status. Our results reinforce the importance of purposefully screening for intimate partner violence during pregnancy and emphasize that mitigating this risk may improve pregnancy outcomes.